Правові засади здійснення громадського контролю за діяльністю Національної поліції - Василенко, В. М.; Vasylenko, V. M. (Право.ua. - 2016. - № 3. - С. 216-224, 2016)
Надано системний аналіз правових положень здійснення громадського контролю за діяльністю Національної поліції України. Вивчено положення основних нормативно-правових актів, які регламентують загальні засади та порядок здійснення окремих форм громадського контролю за діяльністю Національної поліції. Наголошено, що адміністративно-правові норми, як складова правових засад громадського контролю, відіграють ключове значення щодо його здійснення за діяльністю Національної поліції, що проявляється у: беззаперечно більшій їх кількості (закріплені у законах, підзаконних та, зокрема, відомчих нормативно-правових актах); формуванні засад практичної реалізації громадського контролю за діяльністю Національної поліції; встановлені особливостей втілення громадського контролю безпосередньо по відношенню до Національної поліції як на законодавчому, так і відомчому рівнях правового регулювання; існуванні адміністративно-деліктних норм як прояву гарантування реалізації окремих форм громадського контролю.

The article is focused on the systematic analysis of the legal provisions of carrying out public control over the activities of the National Police of Ukraine. The provisions of the basic regulatory legal acts regulating the general principles and procedure for exercising certain forms of public control over the activities of the National Police have been studied. As a result, the author has concluded that administrative and legal norms, as part of the legal principles of public control, play the key role in regard to its implementation under the activities of the National Police, which is manifested in: undoubtedly their more quantity (enshrined in laws, regulations and, in particular, departmental regulatory legal acts); formation of principles of practical realization of public control over the activities of the National Police; established specific features of implementing public control directly in relation to the National Police both at the legislative and departmental levels of legal regulation; the existence of administrative and tort norms as a manifestation of guaranteeing for the implementation of certain forms of public control.

Представлен системный анализ правовых положений осуществления общественного контроля за деятельностью Национальной полиции Украины. Изучены положения основных нормативно-правовых актов, регламентирующих общие принципы и порядок осуществления отдельных форм общественного контроля деятельности Национальной полиции.
Legal principles of carrying out public control over the National Police activities
Keywords: контроль; control; громадський контроль; public control; общественный контроль; правові засади; legal principles; правовые основы; Національна поліція України; National Police of Ukraine; Национальная полиция Украины